'Heads in the Sand': Football, Politics and Crowd Disasters in Twentieth-Century Britain - Martin Johnes (Soccer and Disaster: International Perspectives, 2001)
This chapter explores the policy responses to crowd disasters in UK football stadia. Despite repeated calls from the police and disaster inquiries for the legal regulation of safety in football grounds it was not until 1975 that limited legislation was implemented. The chapter argues that the limited and piecemeal responses were rooted in an apathy towards safety amongst the football authorities, central government and fans. This apathy was underpinned by a desire to exclude sport from legislation, by the terrace culture of the game, by the characterization of fans as hooligans and by the exclusion of the safety of soccer fans from the concerns of central government. The disasters of the 1980s saw the safety legislation extended but it was not until the horrors of Hillsborough that approaches to safety were revolutionised within the football industry. Even then, the financial implications meant there was a reluctance amongst the football authorities to embrace the required measures, while the motive of the Conservative government was more underpinned by a desire to fight hooliganism than to protect the interests of fans.